Correlation of GM-CSF mRNA in bronchoalveolar fluid with indices of clinical activity in sarcoidosis. Issue 12 (December 1993) - Itoh, A; Yamaguchi, E; Furuya, K; Hizawa, N; Ohnuma, N; Kawakami, Y; Kuzumaki, N
Abstract : BACKGROUND--Granulocyte-macrophage colony stimulating factor (GM-CSF) has several proinflammatory effects, some of which potentially favour granuloma formation. Its mRNA expression by the inflammatory cells recovered from lungs of patients with pulmonary sarcoidosis has been previously reported. In this study an association between GM-CSF expression and manifestations of the disease was explored. METHODS--GM-CSF mRNA was detected by reverse transcription polymerase chain reaction in the cells of bronchoalveolar lavage (BAL) fluid of 20 patients with pulmonary sarcoidosis. RESULTS--GM-CSF mRNA expression was positive in 15 of 20 patients with sarcoidosis. Fourteen of the 15 patients with positive mRNA expression had worsening or unchanged disease during the year preceding this study, on the basis of radiographic or physical findings, or both, whereas all five "negative" patients were judged to be improving. Similarly, serum levels of angiotensin converting enzyme, the proportion of lymphocytes in BAL fluid, and the CD4+/CD8+ ratio of lymphocytes in BAL fluid were significantly higher in the positive patients. CONCLUSIONS--There was an association between the presence of GM-CSF mRNA in the cells in BAL fluid and other indices of disease activity in sarcoidosis.